La transición hacia la mediana empresa y el desarrollo exportador: el caso de Acrimetal en el Perú - Roca Tavella, Santiago (2002)
The present case study discusses the relevance of competitive small business as a seed of endogenous productive development and natural way for the emergence of medium-sized enterprises. After analysing the business structure in Peru and identifying the elements that inhibit growth, it examines the origin and trajectory of Acrimetal, a small leading company in the manufacture of mannequins that despite the limitations of the environment has managed to overcome the survival and develop an expectant position to undertake its transition towards medium-sized businesses and export activity. The empirical evidence found allows, through the notion of Schumpeterian underdevelopment, to explain the nature of the risks that Acrimetal and other non-technical industries face when they intend to participate in international trade and direct their efforts to large and high purchasing power markets, where their organization productive and lack of commercial links prevent them from capturing surpluses.